The phenomenon of the growing popularity of the right-wing Eurosceptic party «Alternative for Germany» in modern Europe - Ibragimova Г.Е.; Karamanov А.М. (Bulletin of the L.N. Gumilyov Eurasian National University. Political Science. Regional Studies. Oriental Studies. Turkology Series., 2020)
The article examines the ascent of the party «Alternative for Germany» (AFD) from its creation in 2012 to a sharp jump in popularity in the parliamentary elections in 2017. Special emphasis is paid to the review of the strengthening of Eurosceptic rhetoric, criticism of modern German politics as a result of the arrival of farright politicians to the leading positions in the party. The article concludes that Euroscepticism has become one of the components of the broad populist platform of the party as the AFD has developed. Moreover, it is established that unexpectedly high support for the AFD by the German electorate and the party’s acquisition of the status of the main opposition force in the Bundestag becomes an important factor for the German establishment in the context of defending its position on further deepening the processes of European integration.